Implementation Of Fuzzy Mamdani Method For Bread Production At Aroma 3 Bakery - Efriantho, Dodi; Siswanto, Siswanto (LPPJPHKI Universitas Dehasen Bengkulu, 2025)
Increasing competition in the economic sector of each company in the industry forces companies to be able to beat rivals through inventory management in order to achieve maximum profit. Therefore, product quantity planning is crucial to be able to meet all existing demand. The purpose of this study focuses on the use of the Mamdani type Fuzzy Inference System to determine the amount of bread production based on inventory and demand data at Aroma 3 Bakery. The application is designed using the PHP programming language and MySQL database. The implementation of the Mamdani type Fuzzy logic in determining the amount of bread production based on inventory and demand data can provide support to Aroma 3 Bakery in making decisions for the next production amount.